IoT-Enabled Smart Plant Ecosystem Integrating Real-Time Monitoring, Automated Irrigation, and Intelligent Growth Optimization Frameworks - Md. Safaet Hossain; Israt Jahan; Jawata Afnan; Israt Sultana Tanny; Nashid Sultana Mim; Kayes Mahmood (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2026)
Urban plant care is increasingly important for sustainable living, but many users face inconsistent watering, insufficient care knowledge, unsuitable plant selection and delayed disease recognition. This study presents Easy Grow Plants, an integrated web and Internet of Things (IoT) ecosystem that connects plant care guidance, soil-moisture monitoring, automated watering, plant recommendation, image-based plant health assistance, marketplace functions, community interaction and plant exchange. The prototype was implemented using a React frontend, Django REST backend, SQLite database and an Arduino UNO R4 WiFi smart pot with a soil moisture sensor, relay module and DC water pump. Functional, interface, API, IoT connectivity, sensor calibration, watering control and LAN deployment tests were conducted. The results show that the core modules operated together as an integrated academic prototype. The system demonstrates a practical foundation for smart urban gardening, although cloud deployment, multi-device testing and stronger AI validation remain future improvements